Sulla morte del paesaggio. Dalla natura all’ecologia - Gemmani, Gianluca (Aisthesis, 2025)
The paper aims to elucidate the critical issues that arise from the overlapping of the concepts of environment and landscape. Initially, it contrasts two opposing perspectives: the view held by some scholars, particularly in France, who emphasize the importance of distinguishing the theoretical domain of landscape from other disciplines, such as geography and ecology, and the perspective of those, like A. Carlson, who have proposed the Natural Environmental Model as a means to provide a robust foundation for aesthetic appreciation of nature. The discussion will first demonstrate how the concept of environment is intrinsically linked to a notion of nature that reduces it to its objective and measurable aspects. Subsequently, it will be revealed how this concept is itself a product of landscape aesthetic culture. Finally, the paper will suggest how landscape and ecology intersect in defining the boundary that simultaneously unites and separates nature and culture.